A Simple Staining Method Using Pyronin Y for Laser Scanning Confocal Microscopy to Evaluate Gelatin Cryogels - Brianna Reece; Elizabeth Bahar; Angel Pereira; Lukasz Witek; Katsuhiro Kita (Bio-Protocol)
This study explores the novel application of pyronin Y for fluorescently labeling extracellular matrices (ECMs) and gelatin cryogels, providing a simple and reliable method for laser scanning confocal microscopy. Pyronin Y exhibited remarkable staining ability of the porous structures of gelatin cryogels, indicating its potential as a reliable tool for evaluating such biomaterials. Confocal imaging of pyronin Y–stained cryogels produced high signal-to-noise ratio images suitable for quantifying pores using Fiji/Image J. Importantly, pyronin Y enabled effective dual-color imaging of cryogel-labeled mesenchymal stem cells, expanding its utility beyond traditional RNA assays. Traditional staining methods like Mason’s trichrome and Sirius Red have limitations in cryogel applications. Pyronin Y emerges as a powerful alternative due to its water solubility, minimal toxicity, and stability. Our results demonstrate pyronin Y’s ability to specifically stain gelatin cryogel's porous structures, surpassing its weak staining of ECMs in 2D. Confocal imaging revealed enduring staining even under rigorous scanning, with no notable photobleaching observed. Furthermore, pyronin Y's combination with Alexa Fluor 647 for dual-color imaging showed promising results, validating its versatility in fluorescence microscopy. In conclusion, this study establishes pyronin Y as a cost-effective and rapid option for fluorescent staining of gelatin cryogels. Its simplicity, efficacy, and compatibility with confocal microscopy make it a valuable tool for characterizing and evaluating gelatin-based biomaterials, contributing significantly to the field of cryogel imaging. The study opens new avenues for dual-color imaging in biomaterial research and tissue engineering, advancing our understanding of cellular interactions within scaffolds.